Supporting good practice in the provision of services to people with comorbid mental health and alcohol and other drug problems in Australia: describing key elements of good service models - Canaway Rachel; Lewis Virginia; Merkes Monika (BMC, 2010)
Abstract Background The co-occurrence of mental illness and substance use problems (referred to as "comorbidity" in this paper) is common, and is often reported by service providers as the expectation rather than the exception. Despite this, many different treatment service models are being used in the alcohol and other drugs (AOD) and mental health (MH) sectors to treat this complex client group. While there is abundant literature in the area of comorbidity treatment, no agreed overarching framework to describe the range of service delivery models is apparent internationally or at the national level. The aims of the current research were to identify and describe elements of good practice in current service models of treatment of comorbidity in Australia. The focus of the research was on models of service delivery. The research did not aim to measure the client outcomes achieved by individual treatment services, but sought to identify elements of good practice in services. Methods Australian treatment services were identified to take part in the study through a process of expert consultation. The intent was to look for similarities in the delivery models being implemented across a diverse set of services that were perceived to be providing good quality treatment for people with comorbidity problems. Results A survey was designed based on a concept map of service delivery devised from a literature review. Seventeen Australian treatment services participated in the survey, which explored the context in which services operate, inputs such as organisational philosophy and service structure, policies and procedures that guide the way in which treatment is delivered by the service, practices that reflect the way treatment is provided to clients, and client impacts. Conclusions The treatment of people with comorbidity of mental health and substance use disorders presents complex problems that require strong but flexible service models. While the treatment services included in this study reflected the diversity of settings and approaches described in the literature, the research found that they shared a range of common characteristics. These referred to: service linkages; workforce; policies, procedures and practices; and treatment.